Pengaruh Online Customer Review dan Online Customer Rating Terhadap Keputusan Pembelian Pada Aplikasi Tokopedia Dimoderasi Oleh Kualitas Produk - Virgo Simamora; Dina Maryana (Cakrawala Repositori IMWI, 2023)
This research seeks to explain the moderating effect of product quality on the relationship between online customer reviews and ratings and online purchasing decisions. Unknown number of Tokopedia application users in Jakarta constitute the population for this research. This study used a technique of purposive sampling in which the sample must meet the requirements specified. For data collection, online questionnaires were used in this study. Smart PLS3 software is used for data processing. As a result, 100 Tokopedia application users fulfilled the research criteria and participated in this study. The findings of the research indicate that product quality moderates the impact of online customer reviews on online purchase decisions. Similarly, product quality moderates the impact of online customer ratings on purchase choices made online. The results of this research may give entrepreneurs with information on the online behavior of customers.